Enhanced Trust-nd Protocol To Prevent Temporal Denial-of-service Vulnerabilities On Ipv6 Link-local Network - Hasbullah, Iznan Husainy (2023)
Trust-ND is a trust-based distributed security mechanism to secure IPv6 link-local networks as an alternative to the highly complex Secure Neighbor Discovery (SEND) protocol. However, theoretical analysis and experimental research revealed that the Trust-ND protocol is susceptible to temporal Denial-of-Service vulnerabilities due to timestamp reference, field size and format, and verification rule. This research aims to prevent temporal DoS vulnerabilities on IPv6 link-local networks by enhancing Trust-ND without jeopardizing its original structure to retain its advantages over SEND. The proposed enhanced version of Trust-ND, called eTrustND, addresses the vulnerabilities in three stages, (i) Timestamp Formulation, (ii) Enhanced Trust-ND, and (iii) Rule-based verification mechanism. The first stage changes the reference time from system time to UTC, the 24-hour time format in hexadecimal to epoch second in integer. It also increases the precision from one hundredth to one ten-thousandth second. The second stage utilizes the Trust-ND’s Reserved field for the sub-second value and changes the timestamp field data type from byte to IntField. The third stage proposes a rule-based verification mechanism to handle out-of-sync computer clocks, preventing temporal DoS vulnerabilities. The experiment results on a testbed demonstrate that eTrustND prevents temporal-based DoS vulnerabilities without jeopardizing the original Trust-ND packet structure and adding overheads (computation and bandwidth).